2022
DOI: 10.1111/acer.14813
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic organization of open field behavior following moderate prenatal alcohol exposure

Abstract: Background Prenatal alcohol exposure (PAE) can produce deficits in a wide range of cognitive functions but is especially detrimental to behaviors requiring accurate spatial information processing. In open field environments, spatial behavior is organized such that animals establish “home bases” marked by long stops focused around one location. Progressions away from the home base are circuitous and slow, while progressions directed toward the home base are non‐circuitous and fast. The impact of PAE on the orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 89 publications
1
11
1
Order By: Relevance
“…In the present study, mPAE and SACC rats were given a single 30-min exposure to an open field in a testing room that was made completely dark. Consistent with previous reports (Donaldson et al, 2019;Osterlund Oltmanns et al, 2022), we found that general locomotion decreased across the test session as measured by a reduction in travel distance, an increased stop duration, and a progressive increase in stops located along the edge of the maze environment. As expected, progression features (path directness) also varied with the length of the trip such that shorter trips were associated with more direct progressions and a more consistent topography relationship between progression peak speeds.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, mPAE and SACC rats were given a single 30-min exposure to an open field in a testing room that was made completely dark. Consistent with previous reports (Donaldson et al, 2019;Osterlund Oltmanns et al, 2022), we found that general locomotion decreased across the test session as measured by a reduction in travel distance, an increased stop duration, and a progressive increase in stops located along the edge of the maze environment. As expected, progression features (path directness) also varied with the length of the trip such that shorter trips were associated with more direct progressions and a more consistent topography relationship between progression peak speeds.…”
Section: Discussionsupporting
confidence: 92%
“…PAE (moderate or high doses) can also alter the expression of anxiety-like behaviors in open environments (Osborn et al, 1998;Staples et al, 2013;Wang et al, 2023). It is important to note, however, that in our previous work using a lighted open field (Osterlund Oltmanns et al, 2022), we failed to detect group differences in the percentage of stops localized along the edge of the open field (a putative anxiety-like phenotype). Additional work is therefore needed to investigate this possibility using a battery of tests for anxiety-like behavior (e.g., elevated plus maze).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations